(untitled) (Materiali di Estetica. Terza serie, 2016)
Remembering and thinking the intellectual experience of Guido Davide Neri leads to face up to the philosophy issue: yesterday (not just Guido’s education and teaching period, but even his philosophical one to which he dedicated his most explicit book on the topic: Aporie della realizzazione) and today. Guido Neri found in Patocka and in Kosik especially a very living theoretical philosophy that had the painful chance to become active in a political way. Probably, Guido Neri has gone on testing this philosophical model, working on Husserl and Merleau-Ponty, until his last studies on Caravaggio, turning it into his work’s program: a phenomenology of perception is an essential part of a philosophy history. One thing is certain: nowadays for the uncertain philosophy it won’t be easy to forget this program.